The Development of the Dribbling Training Model for U-18 Football Players Gelora Baru Lagan Jaya - Maldin Ahmad Burhan; Muhamad Sukron; M. Dandi Fauzi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
This study aims to develop a more varied, valid, practical and effective dribbling training model for U-18 soccer players. Based on these problems, the researchers developed a dribbling training model in the new surge soccer club game, Lagan Jaya Dharmasraya. Model development uses the ADDIE model which consists of 5 stages, namely, analysis (analyze), design (design), development (development), implementation (implementation), evaluation (evaluation). The five stages were carried out through analysis of training programs, material analysis, and analysis of student characteristics. Then the validation test was carried out by 2 validators (team of experts), the language test and the practicality test by the football coach and 15 players from the new surge soccer club Lagan Jaya Dharmasraya. After the model is categorized as valid and practical, an effectiveness test is then carried out by doing soccer dribbling exercises. The results of the research on the development of the dribbling training model for soccer players U-18 new gelora jaya Dharmasraya in the validity test obtained percentage data with an average of 89.6% categorized as very valid, practicality test by soccer coach with a percentage of 92% and test practicality by players has a percentage of 80% and effectiveness with a percentage of 80% is categorized as effective. Based on the results that have been obtained, the dribbling training model for the u-18 soccer player new surge Lagan Jaya Dharmasraya is categorized as valid, practical, and effective. It can be concluded that the dribbling training model for the new surge u-18 soccer player Lagan Jaya Dharmasraya can be applied